Proving It To Others Or Proving It To You: Motivating Students To Initiate And Develop Healthy Levels Of Physical Activity Using Extrinsic And Intrinsic Appeals (2011)
Integrating Self-Determination Theory, the Trans-Theoretical Model of Change and extant research on health-related choices, I suggest that persuasive communications aimed at inducing greater physical activity will be more effective if they are tailored to match the target‘s exercise status. Whereas sedentary people can be better persuaded to exercise by appealing to extrinsic motives, active people can be better persuaded to increase physical activity by appealing to intrinsic motives. I tested this suggestion by presenting college students with made-up magazine articles framed to prime different types of motivational appeals. In a first study, conducted at a private university in Colombia, I found that while the intrinsic motive of competence (proving to yourself that you can do something) is a more powerful motivator for active students than the extrinsic motive of recognition (proving to others that you can), as judged by steps walked and self-reported exercise, the reverse is true for sedentary students.